GYNECOLOGICAL EVALUATION OF PELVIC MASSES IN ULTRASONOGRAPHY FOR THE REPRODUCTIVE AGES OF FEMALES (Journal of Medical & Health Sciences Review, 2025)
Background: Ultrasonography is the first line technique to evaluate and characterize the different types of common and advance pathologies by imaging. In this study 30 females investigated to rule out the gynecologic origin pelvic masses by ultrasonography. A standardized terminology, high-frequency and 3D Doppler and transvaginal could improve diagnostic performance by allowing a better assessment of gynecological masses in reproductive ages of females.Objective: To review the evaluation and characterization of pelvic masses of gynecological origin by ultrasonography in reproductive age of females, arrange to consider the specific findings which are helpful for the preoperative diagnosis.Material and Methods: Using search engines a literature search was carried out. We sourced the paper of this research from the NCBI, PubMed, Medline, Medscape, and Google scholar. There were a total 30 publications include in this research. The methods used for patients’ evaluation include through clinical examination and radiographic study. This research aimed to assess the imaging symptoms of pelvic masses in females.Results: The most common radiographic features in this study is present in following conditions: Endometriosis(6.67% ) , Adnexa(pelvis masses)(50%) , Cul de sac( 3.33% ), Ovarian cyst(13.33% ), Follicular cyst( 13.33%), Polycystic(13.33%) and Fibroids,(23.33%)                                                                                                                                             The most common radiographic features in this study is absent in following conditions: Endometriosis(93.33% ), Adnexa(pelvis masses)(50%), Cul de sac( 96.66% ), Ovarian cyst(86.66% ), Follicular cyst( 86.66%), Polycystic(86.66%) and Fibroids (76.66% )Conclusion: The most common radiographic features in this study is endometriosis, adnexa (pelvic masses), Cul de sac , ovarian cyst, follicular cyst, polycystic and fibroids. These all findings are present in female patients.